Comparative bibliometric analysis of the scientific activity of the CSIC and four European counterparts: CNRS, HG, MPG and CNR (2006-2015) - Maldonado Carrillo, Jairo; Montesi, Michela (Revista General de Información y Documentación, 2018)
The article presents the research activity of the Spanish Consejo Superior de Investigaciones Científica (CSIC) during the period 2006-2015 in comparison with similar European institutions, i.e. the Centre National de la Recherche Scientifique (CNRS), the Helmholtz-Gemeinschaft (HG), the Max-Planck-Gesellschaft (MPG), y the Consiglio Nazionale delle Ricerche (CNR). Using data from Scopus, production, impact and collaboration are analyzed. Specifically, the following indicators are produced: number of publications and activity index, for the research activity indicators; number of citations and citations per publication, percentage of no cited items, h-index and immediacy index, for the impact indicators; and, finally, frequency of international collaboration and international collaboration index, for the collaboration indicators. Results show differences among the five research centers in all the three dimensions studied. The CSIC appears to be the institution that achieves the best budget-production-impact balance. The other institutions all stand out in different aspects, such as total production (CNRS), impact (MPG), degree of specialization (HG), or limited international collaboration (CNR).